Implementasi Sistem Pakar Untuk Diagnosis Penyakit Tomat: Pendekatan Backward Chaining Berbasis Web - Wijaya, Taruma Leo; Fryonanda, Harfebi; Mardiah, Ainil; Defni, Defni; Ibrahim, Roy (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to implement an expert system using a web-based backward chaining method approach to help farmers diagnose and manage tomato plant diseases. This study was conducted because diagnosing plant diseases requires the help of agricultural experts, which causes problems with consultation costs and farmers who have difficulty knowing the type of disease in tomato plants will cause losses for farmers due to crop failure. The methodology used in this study is the prototype method which begins with identifying problems through data collection from literature, interviews with agricultural experts, and field observations. The collected data is then analyzed using the backward chaining method to trace symptoms to the cause of the problem and provide recommendations for handling. This system is implemented in the form of a web application that facilitates access for farmers. The results of the study show that this expert system is able to provide accurate and reliable diagnoses and recommendations with an accuracy level of this study of 85%. Thus, this expert system is expected to improve farmers' knowledge and skills in managing tomato plants, as well as contribute to increasing yields and the quality of agricultural products